[tex]a)2x + 3 = - 5[/tex]
[tex]2x = - 5 - 3[/tex]
[tex]2x = - 8[/tex]
[tex]x = - \frac{8}{2} [/tex]
[tex]x = - 4 \: \in\: \mathbb{Z}[/tex]
[tex]b)3(x - 1) = - 3[/tex]
[tex]3x - 3 = - 3[/tex]
[tex]3x = - 3 + 3[/tex]
[tex]3x = 0[/tex]
[tex]x = \frac{0}{3} [/tex]
[tex]x = 0 \: \in \: \mathbb{Z}[/tex]
[tex]c)4(x + 2) = 3x - 6[/tex]
[tex]4x + 8 = 3x - 6[/tex]
[tex]4x - 3x = - 6 - 8[/tex]
[tex]x = - 14 \: \in \: \mathbb{Z}[/tex]
[tex]d)8x - 16 = 0[/tex]
[tex]8x = 0 + 16[/tex]
[tex]8x = 16[/tex]
[tex]x = \frac{16}{8} [/tex]
[tex]x = 2 \: \in \: \mathbb{Z}[/tex]
[tex]e) - 4x + 2 = - 30[/tex]
[tex] - 4x = - 30 - 2[/tex]
[tex] - 4x = - 32 \: | \div ( - 4)[/tex]
[tex]x = 8 \: \in \: \mathbb{Z}[/tex]